Internal Medicine: a short comment - Pais, Maria João (1997)
The author briefly discusses the problems which arise today in the speciality of Internal Medicine, highlighting the important unifying role which it performs against a background of increasing super-specialization, and furthermore the need to redefine its scope of action as a speciality.